Research papers in the Ceylon Medical Journal between 2009 and 2018: A scientometric analysis - Johoran, S. Shabnam (The Library, University of Colombo, 2019)
A scientometric analysis of research articles published in the Ceylon Medical Journal was carried out with the objectives of 1) mapping the year-wise distributions of papers, 2) examining the authorship patterns and 3) determining the degree of collaboration between the authors. Ten volumes of the said journal containing 40 issues from 2009 -2018 were considered for the present study. Only the research articles (230) published in these 40 issues were considered and others were excluded from the study. Findings revealed that the highest number of research articles (33) were published in 2017 with a gradual increase, except in 2018 where a marginal decrease is found. Out of the 230 contributions, only 23 papers (10%) are single authored and the rest (90%) are multi authored. The highest number of multi- authored papers (28) were published in the year 2017. The average degree of collaboration is 0.90 during the study period, which indicates that there was a high level of collaboration between authors. Out of the 230 research articles, the majority (196, 85.22%) were published by Sri Lankan authors and only 14 articles (6.09%) were published by international authors. It seems that there was a minimal collaboration of Sri Lankan authors with foreign authors (8.70%). Authors from countries such as the United States, Japan, Australia, Malaysia, India, Hong Kong, United Kingdom, New Zealand, Singapore, Nigeria, Finland, Norway and Turkey have contributed to this journal. The highest number of author contribution is from India, consisting of 20 authors followed by the United Kingdom with contributions by 11 authors. This study concludes that the majority of the research papers are by multi authors and by the Sri Lankan authors. The degree of collaboration indicates that there is a high degree of author collaboration. The level of foreign collaboration is minimal. This study may help those who wish to map the scientometric patterns of journals.
Keywords: authorship pattern, Ceylon Medical Journal, degree of collaboration, Scientometric analysis